Calbindin D28k distribution in neurons and reactive gliosis in cerebellar cortex of natural Rabies virus–infected cattle. (July 2016) - Verdes, José Manuel; de Sant'Ana, Fabiano José Ferreira; Sabalsagaray, María Jesús; Okada, Kosuke; Calliari, Aldo; Moraña, José Antonio; de Barros, Claudio Severo Lombardo
Rabies has been an enigmatic disease because microscopic findings in central nervous system tissues do not always correlate well with the severity of the clinical illness. Immunohistochemical staining of the calcium-binding protein calbindin (specifically CbD28k) seems to be the technique most used to identify Purkinje neurons under normal and pathological conditions. In the present work, we evaluated CbD28k immunoreactivity in the cerebellar cortex of normal and natural Rabies virus (RABV)-infected cattle. We examined brains from 3 normal cows and from 6 crossbreed cattle with a histologic diagnosis of rabies. Samples were taken from the cerebral cortex, cerebellum, hippocampus, and brainstem. Immunohistochemistry was carried out using the following primary antibodies: anti-RABV, anti-GFAP, and anti-CbD28k. In the cerebellar cortex, RABV infection caused the loss of CbD28k immunostaining in Purkinje cells; some large interneurons in the granular layer maintained their positive CbD28k immunoreaction. The identification of this loss of CbD28k reactivity in cerebellar Purkinje cells of RABV-infected cattle presents a potentially valuable tool to explore the impairment of Ca 2+ homeostasis. In addition, this may become a useful method to identify specific molecular alterations associated with the higher prevalence of Negri bodies in Purkinje cells of cattle. Furthermore, we detected the presence of rabies viral antigens in different regions of the central nervous system, accompanied by microglial proliferation and mild reactive astrogliosis.